(untitled) (Research, Society and Development, 2021)
This work aims to present the process of developing a didactic application in the classroom. For the application of this experiment, video was used as a teaching-learning tool. For the methodological process we will approach the critical-dialectical model, in the terms of Gamboa (2013). Guided by authors: Betetto (2011), Ferreira (1975), Moran (1995), Moreira (2006), Rosado (2016), Vogel (2015), who advocate the use of audiovisual material as an educational tool. As well as endorsed in the Theory of Meaningful Learning, we created two videos to assist the learning of financial mathematics in a 9th grade class at a public school in the city of Caiapônia - GO with the aim of analyzing the potential of using video in the classroom as a didactic resource for teaching topics related to financial mathematics. In order to evaluate the students’ teaching-learning process in relation to the content, the students created their own videos addressing the theme “Financial mathematics in my daily life”, in which real situations were discussed that demonstrated the application of the contents seen in class of class. With the exposure of the videos produced by the students, and the methodologies used in this activity, they attested that the video, used as a didactic tool in an appropriate way, can contribute significantly to the teaching-learning of the schoolchildren.